Terror trips - Stine, R. L.; Keenan, Sheila (Goosebumps graphix, 2007)
Presents graphic novel adaptations of three of R.L. Stine's books; including "One Day at Horrorland," "A Shocker on Shock Street," and "Deep Trouble."